Financial Optimization in the Automotive Industry: Leveraging Cloud-Driven Big Data and AI for Cost Reduction and Revenue Growth - Lakshminarayana Reddy Kothapalli Sondinti; Ravi Kumar Vankayalapati; Shakir Syed; Ramanakar Reddy Danda; Rama Chandra Rao Nampalli; Kiran Kumar Maguluri; Yasmeen (The Bioscan, 2024)
This research delves into the use and reference of artificial intelligence (AI) technology by Indian banks and how they affect their operational process. It also looks at how financial performance is affected by the disclosure of AI-related terminology. The distribution of AI and associated information in the textual data of the annual report is examined using content analysis. Using content and regression analysis, the research shows that disclosure of AI-related phrases has been steadily increasing in the annual reports of Indian banks. It seems that several Indian banks continue to be in the early phases of adopting and deploying AI technology, since their degree of transparency about AI is still inadequate. The findings suggest that the publication of AI-related terms impacts the financial performance of institutions. This conclusion is in line with previous research showing that AI increases revenue and decreases costs, and it also supports the popular view that AI enhances accounting efficiency in the areas of ROA and ROE while having a negative impact on overall expenditures. The research of AI voluntary disclosure is an expanding field, and this work adds to it in several ways. To begin with, it makes it possible to objectively evaluate AI's utility by creating an artificial intelligence disclosure index which tracks the current state of AI implementation. Secondly, it sheds light on how financial success relates to AI disclosure. Third, it emphasises the requirement for disclosure guideline rules and supports the work of legislators, international agencies, and supervisory organisations to solve AI disclosure challenges. Lastly, it contributes to the automotive banking industry's practitioners who are implementing AI-driven operational transformations and lends credence to the need for more AI transparency and well-informed decision-making that is in line with financial institutions' goals.